118 UMPSA ROTU Second Lieutenants commissioned in 43rd ROTU Commissioning Ceremony Year 2025 - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
SERDANG, 13 September 2025 - A total of 118 UMPSA ROTU Second Lieutenants were commissioned during the 43rd Commissioning Ceremony Parade of the Army, Navy, and Air Force Reserve Officers Training Unit (ROTU) Year 2025, which took place at Universiti Putra Malaysia (UPM), Serdang.